JUDICIAL CORRUPTION DAN PEMBAHARUAN HUKUM PIDANA - Yudi Kristiana (Fakultas Hukum Universitas Kristen Indonesia, 2016)
The phenomenon of judicial corruption in all its forms by receiving bribe in the judicial process is a reality that is shameful in the history of law in Indonesia. The serious impact will occurred in economy and politic including in the law because judicial corruption will reduce the dignity, credibility, public tust and also the purpose of law. To address judicial corruption, the reform of the Penal Code is done by: (1)reorientation of the focus of criminal law reform and legal structure legal substance to the legal culture; (2) The criminal law reform that emphasizes the substantial justice of the procedural justice; and (3)reform of criminal law with a progressive approach to the law.Kata Kunci: judicial corruption, pembaharuan dan hukum progresif